Evaluation of a Commercial Culture-Free Neutralization Antibody Detection Kit for Severe Acute Respiratory Syndrome-Related Coronavirus-2 and Comparison With an Antireceptor-Binding Domain Enzyme-Linked Immunosorbent Assay. (30th April 2021) - Papenburg, Jesse; Cheng, Matthew P; Corsini, Rachel; Caya, Chelsea; Mendoza, Emelissa; Manguiat, Kathy; Lindsay, L Robbin; Wood, Heidi; Drebot, Michael A; Dibernardo, Antonia; Zaharatos, Gerasimos; Bazin, Reneé; et al.
Abstract: Background: Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) surrogate neutralization assays that obviate the need for viral culture offer substantial advantages regarding throughput and cost. The cPass SARS-CoV-2 Neutralization Antibody Detection Kit (GenScript) is the first such commercially available assay that detects antibodies that block receptor-binding domain (RBD)/angiotensin-converting enzyme (ACE)-2 interaction. We aimed to evaluate cPass to inform its use and assess its added value compared with anti-RBD enzyme-linked immunosorbent assays (ELISAs). Methods: Serum reference panels comprising 205 specimens were used to compare cPass to plaque-reduction neutralization test (PRNT) and a pseudotyped lentiviral neutralization (PLV) assay for detection of neutralizing antibodies. We assessed the correlation of cPass with an ELISA detecting anti-RBD immunoglobulin (Ig)G, IgM, and IgA antibodies at a single timepoint and across intervals from onset of symptoms of SARS-CoV-2 infection. Results: Compared with PRNT-50, cPass sensitivity ranged from 77% to 100% and specificity was 95% to 100%. Sensitivity was also high compared with the pseudotyped lentiviral neutralization assay (93%; 95% confidence interval [CI], 85–97), but specificity was lower (58%; 95% CI, 48–67). Highest agreement between cPass and ELISA was for anti-RBD IgG ( r = 0.823). Against the pseudotyped lentiviral neutralization assay, anti-RBD IgG sensitivity (99%; 95% CI, 94–100) was very similar to that of cPass, but overall specificity was lower (37%; 95% CI, 28–47). Against PRNT-50, results of cPass and anti-RBD IgG were nearly identical. Conclusions: The added value of cPass compared with an IgG anti-RBD ELISA was modest. Abstract : The results of the current evaluation demonstrate the ability of cPass SARS-CoV-2 Neutralization Antibody Detection Kit (GenScript) to detect blood specimens with anti-SARS-CoV-2 neutralizing antibodies. However, the added value of the cPass compared with an IgG anti-RBD ELISA was modest.